Queer temporalitet: et forskningshistorisk rids - Aagard Friis, Joachim (Slagmark - Tidsskrift for idéhistorie, 2021)
This article explores the concept of queer temporality in the works of queer theorists Lee Edelman, Jack Halberstam, and José Muñoz and establishes a connection between a Marxist critique of abstract capitalist time and queer theory’s critique of the notion of future-oriented social value. Thereby, it shows how economic and social reproduction are both processes that involve a linear and progress-oriented temporality. Edelman uses the concept of reproductive futurism to criticize society’s focus on the child as the ultimate future-oriented goal and argues that queer communities must completely abandon a concept of the future because it is always already embedded in the idea of reproduction. Halberstam examines queer countercultures to find an alternative to Edelman’s anti-social stance, and Muñoz creates a concept of a queer utopia as a future of potentiality that offers hope in the present. The article points out the lack of a sense of history in these theorists’ works on queer temporality and suggests an understanding of the concept that actively incorporates the past as a relevant strengthening of queer communities.